Isozymic variability in a Brazilian collection of annatto (Bixa orellana L.) - de Carvalho, Jane Fiuza Rodrigues Portela; Robinson, Ingrid Peters; Alfenas, Acelino Couto (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objectives of this work were to optimize the isozyme electrophoresis technique for Bixa orellana, and use isozyme markers for a preliminary survey on the genetic variability in Brazilian annatto germplasm accessions. Collection consisted of seed samples from sixty open pollinated trees, representing two Northern and four Southern geographic provenances. The extraction, electrophoresis, and interpretation of annatto isozymes are described. Three out of the twenty-one identified isozyme loci were polymorphic in the collection. The percentage of polymorphic loci (P = 21.05) and the expected heterozygosity in annatto (HT = 0.064) were low, compared to other tropical woody species. A UPGMA phenogram, constructed with Nei's genetic distances, clearly separated the germplasm provenant from North and Central Brazil. Variability was significantly higher among the accessions from Maranhão. A sharp genetic differentiation was detected between accessions from Maranhão and Pará States, despite their geographical proximity. The distinctive isozyme polymorphism, observed in the accessions from Maranhão, together with reports on local morphological heterogeneity in annatto fruit shape, color, and pubescence, calls for more detailed genetic and taxonomic investigation.